Desconstruindo a ciência aberta: desafios, visoes e distopias - Sayão, Luís Fernando (2025)
Context: Open science practices combined with advances in digital technologies have contributed to expanding the frontiers of knowledge, while incorporating into its premises the idea of ÔÇïÔÇïa more collaborative, inclusive and transparent science, with the purpose of accelerating scientific progress. Problem: However, despite the broad recognition by the scientific community, governments and society of the advantages and motivations of open science, significant barriers and contradictions of various natures stand in the way of the promises of open science. Objective: This essay aims to understand, analyze and structure the various aspects and elements of the discourse of what we call open science and its visions, challenges and contradictions. Methodology: The foundations for this discussion are the various documents produced by national and international agencies, as well as by the authors who have focused on this complexity. Result: As a result, the study lists the necessary items for the construction of infrastructural conditions that align transversal requirements necessary for the establishment of a sustainable technical, political and normative framework favorable to the practices, actions and workflows necessary for the transition to open science. Conclusion: It is concluded that open science is, in fact, a field of plural nature, which requires articulation between multiple dimensions of thought and practice.